A study on factors associated with glycemic control among patients with type 2 diabetes mellitus in Hospital Universiti Sains Malaysia - Maira, Hassan (2008)
Prevalence of diabetes is increasing while complication rates and associated diseases amongst diabetics are significantly high. Majority of our patients are still having problem in controlling their blood glucose. The objective of this study was to compare the associated factors of glycemic control among type 2 diabetes patients in Hospital Universiti Sains Malaysia (HUSM).From this study it showed that: A) There was a significant association between; Glycemic status and age of onset of diabetes whereby younger age at onset predispose to poor control of diabetes (p < 0.001). Glycemic status and treatment modalities, whereby insulin users have higher chances to have poor control blood sugar (p = 0.003). Glycemic status and the number of OHA used, whereby the more number of OHA usage increased likelihood to have poorer glycemic control (p < 0.001). Glycemic status with obesity where by the higher BMI of patients, the higher the chances to be poorly control. The prevalence of complications in both cases and controls are comparable. This study provides few factors which can identity subgroup of patients which are high risk to disease morbidity and mortality. Barriers that prevent these patients from meeting their goals must be explored to improve health outcomes. METHODOLOGY: A case-control study and matched with duration of diabetes comparing patients in good glycemic control and patients in poor glycemic control groups were carried out. One hundred and ten patients in each group who were on fol'l ow up in Diabetic Centre, HUSM from December 2005 till December 2006 were selected for the study. The information regarding patient's demographic, medical history and health status were obtained from patients' folder using a structured check list. The data were analyzed using SPSS version 12.0.